Disparitas Penerapan Sanksi Terhadap Putusan Hakim Dalam Perkara Pemalsuan Surat - Gailea, Sitti Wahyuni; Imran, Suwitno Yutye; Moha, Mohamad Rivaldi (Media Hukum Indonesia (MHI), 2025)
The criminal law system in Indonesia provides freedom for judges to determine the amount of the crime in a case. This often results in criminal disparities, where the same criminal act can be given different criminal sanctions. As happened in Decision Number 74/Pid.B/2022/Pn. Gto with Decision Number 201/Pid.B/2024/Pn.Sgt, where Decision Number 74/Pid.B/2022/Pn. Gto has a verdict of ten months in prison, while Decision Number 201/Pid.B/2024/Pn.Sgt has the result of a verdict of two months in prison. This research uses a normative method with a legislative approach and court decisions. The results of the study show that the judge considers several factors, namely the legal subject who feels aggrieved, the losses of the related parties, modus operandi, aggravating circumstances, and mitigating circumstances. This causes the judge's decision for the letter forgery case to have a different verdict.